2015
DOI: 10.1017/s0029665115004164
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D modulates adipose tissue biology: possible consequences for obesity?

Abstract: Cross-sectional studies depict an inverse relationship between vitamin D (VD) status reflected by plasma 25-hydroxy-vitamin D and obesity. Furthermore, recent studies in vitro and in animal models tend to demonstrate an impact of VD and VD receptor on adipose tissue and adipocyte biology, pointing to at least a part-causal role of VD insufficiency in obesity and associated physiopathological disorders such as adipose tissue inflammation and subsequent insulin resistance. However, clinical and genetic studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 127 publications
(199 reference statements)
1
42
0
Order By: Relevance
“…The authors observed that 1,25(OH) 2 D 3 redirects mesenchymal lineage progenitor cells toward adipogenesis. Similar findings were observed in studies using human preadipocytes, which differentiated into mature adipocytes in response to 1,25(OH) 2 D 3 treatment . Other in vitro studies showed that 1,25(OH) 2 D 3 was able to inhibit adipogenesis in the mouse preadipocyte cell line 3T3‐L1 .…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The authors observed that 1,25(OH) 2 D 3 redirects mesenchymal lineage progenitor cells toward adipogenesis. Similar findings were observed in studies using human preadipocytes, which differentiated into mature adipocytes in response to 1,25(OH) 2 D 3 treatment . Other in vitro studies showed that 1,25(OH) 2 D 3 was able to inhibit adipogenesis in the mouse preadipocyte cell line 3T3‐L1 .…”
Section: Introductionsupporting
confidence: 85%
“…Similar findings were observed in studies using human preadipocytes, which differentiated into mature adipocytes in response to 1,25(OH) 2 D 3 treatment. [7,8] Other in vitro studies showed that 1,25(OH) 2 D 3 was able to inhibit adipogenesis in the mouse preadipocyte cell line 3T3-L1. [9,10] In vivo data obtained from vitamin D receptor (Vdr) deficient mice, an animal model that emulates vitamin D deficiency, indicated that these mice developed smaller deposits of subcutaneous and visceral adipose tissues than wildtype (WT) mice.…”
Section: Introductionmentioning
confidence: 99%
“…AT represents not only the main site of vitamin D accumulation in humans, but also a main target of vitamin D action. AT-vitamin D hydroxylases are capable of locally converting this hormone in its active forms [25,26] which display autocrine and paracrine immunoregulatory actions through the specific vitamin D receptor [27,28]. It is plausible, indeed, that chronic DPP4 inhibition modulates AT inflammation and stimulates vitamin D activation/mobilization from adipocytes into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Recently, meta-analyses based on cross-sectional and observational studies strongly suggested that the prevalence of vitamin D deficiency was significantly different between control and obese group. 29,30 Although the cross-sectional studies supported an increase in insulin sensitivity following vitamin D supplementation, 31 the meta-analyses 29,30 did not show any weight reduction in obese patients. Yet, intermediate biomarker of obesity demonstrated an inverse relationship between adiposity and low vitamin D levels.…”
Section: Potential Role Of Vitamin D In Obesitymentioning
confidence: 97%